The Differential Effects of Anger and Sadness on Intertemporal Choice: An ERP Study - Suo, Tao; Jia, Xuji; Song, Xiyan; Liu, Lei (Frontiers in Neuroscience, 2021)
Previous research has taken a valence-based approach to examine the carryover effects of incidental emotions on intertemporal choices. However, recent studies have begun to explore the effects of specific emotions on intertemporal choices. In the study, we investigated how anger and sadness influenced on intertemporal choices by using event-related potentials (ERPs). Behavioral results showed that, compared with neutral prime, anger prime was associated with more preference for delayed rewards, whereas sad prime did not change individuals’ choice preference. Especially, anger prime yielded shorter response time than sad prime for the difficult-to-selecting choices. ERPs results found that, compared with neutral and sad primes, anger prime elicited larger P1 in the fronto-central and parietal areas, larger P2 in the fronto-central area, and larger P3 in the parietal area during the evaluation stage. These findings suggest that there are differential carryover effects of anger and sadness on intertemporal choice.